Using Provider Performance Incentives to Increase HIV Testing and Counseling Services in Rwanda - de Walque, Damien; Gertler, Paul J.; Bautista-Arredondo, Sergio; Kwan, Ada; Vermeersch, Christel; de Dieu Bizimana, Jean; Binagwaho, Agnès; Condo, Jeanine (World Bank, Washington, DC, 2013)
Paying for performance provides financial rewards to medical care providers for improvements in performance measured by specific utilization and quality of care indicators. In 2006, Rwanda began a paying for performance scheme to improve health services delivery, including HIV/AIDS services. This study examines the scheme's impact on individual and couples HIV testing and counseling and using data from a prospective quasi-experimental design. The study finds a positive impact of paying for performance with an increase of 6.1 percentage points in the probability of individuals having ever been tested. This positive impact is stronger for married individuals: 10.2 percentage points. The results also indicate larger impacts of paying for performance on the likelihood that the respondent reports both partners have ever been tested, especially among discordant couples (14.7 percentage point increase) in which only one of the partners is HIV positive.